Síndrome de Escápula Crepitante - Morgado, S (2010)
Snapping Scapula Syndrome is a rare disorder that consists mainly in an audible and/or palpable crepitus of the scapula with movements on the scapulo-thoracic plane. This crepitus is often associated with shoulder or cervicodorsal pain. Patients generally seek medical help for pain relief. This syndrome can have many causes, originating from the various anatomical structures involved in the scapulothoracic movement (bone, muscle, bursa…). The diagnosis is clinical, although imaging studies can be helpful in the identification of the underlying cause. Most patients with Snapping Scapula Syndrome are treated conservatively, with a rehabilitation program and analgesic medication. Surgical approach can be beneficial in patients that do not respond to the nonoperative treatment, although its execution is still not consensual. The authors present the case of a patient with Snapping Scapula Syndrome, its diagnostic and therapeutic approach and a revision of the literature on this pathological entity.